Identification of Road Damage Using the Bina Marga Method - Rendi Nurhakim; Nadhya Susilo Nugroho; Cece Suhendi; Dio Damas Permadi; Utamy Sukmayu Saputri (Universitas KH. Abdul Chalim Mojokerto, 2026)
Roads are land transportation infrastructure comprising all components of the roadway, including complementary structures and facilities intended for traffic. The Cianjur–Sukabumi Connector Road is classified as a primary collector road that serves as an access route for road users traveling from Cianjur Regency to Sukabumi Regency/City. Observations were conducted along the Cianjur–Sukabumi connector road at KM 83+850 – 84+850 (1,000 m). These observations focused on identifying road damage and were carried out using a quantitative approach with calculations based on the Bina Marga method. Based on field observations, several types of pavement distress were found along the Cianjur–Sukabumi connector road, including ravelling, patches, longitudinal cracks, potholes, edge cracking, and longitudinal ruts or rutting. The average traffic volume (LHR) recorded was 6,933.4 pcu/day, placing the road in traffic class 6, with a calculated road condition value of 1.2. The analysis using the Bina Marga method produced a Priority Order (UP) value of 9.8, indicating that the segment falls under routine and preventive maintenance programs. Routine maintenance includes surface layer treatment and pavement repairs that do not aim to increase structural strength, and such activities are implemented throughout the year.